Open Source Software for Mapping Human Impacts on Marine Ecosystems with an Additive Model. Issue 1 (7th June 2016) - Stock, Andy
This paper describes an easy-to-use open source software tool implementing a commonly used additive model (Halpern et al., Science, 2008) for mapping human impacts on marine ecosystems. The tool has been used to map the potential for cumulative human impacts in Arctic marine waters and can support future human impact mapping projects by 1) making the model easier to use; 2) making updates of model results straightforward when better input data become available; 3) storing input data and information about processing steps in a defined format and thus facilitating data sharing and reproduction of modeling results; 4) supporting basic visualization of model inputs and outputs without the need for advanced technical skills. The tool, called EcoImpactMapper, was implemented in Java and is thus platform-independent. A tutorial, example data, the tool and the source code are available online.